Komposisi Sarabande Sebuah Analisis Semiotika Musik - Yensharti Yensharti (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2009)
Sarabande is one piece of music that was created in the 17th century. GF Haendel make this composition for the organ instrument. The signs or symbols embodied in the form of visual Sarabande sheet music can be used as a material for sound analisys from the perspective of semiotics. Signs that present a representative acoustic sound and also can give another meaning beyond the sign itself.